The European Medicines Agency Review of Tafasitamab in Combination With Lenalidomide for the Treatment of Adult Patients With Relapsed/Refractory Diffuse Large B-cell Lymphoma. Issue 12 (18th December 2021) - Delgado, Julio; Papadouli, Irene; Sarac, Sinan B.; Moreau, Alexandre; Hovgaard, Doris; Gisselbrecht, Christian; Enzmann, Harald; Pignatti, Francesco
Abstract : Tafasitamab is a humanized monoclonal antibody that binds to the CD19 antigen, which is expressed in tumor cells from patients with diffuse large B-cell lymphoma (DLBCL). On June 24, 2021, a positive opinion for a conditional marketing authorization was issued by the European Medicines Agency (EMA)'s Committee for Medicinal Products for Human Use (CHMP) for tafasitamab, in combination with lenalidomide, for the treatment of adult patients with relapsed or refractory DLBCL who are ineligible for autologous stem cell transplantation. Tafasitamab was evaluated in the phase 2 single-arm, multicenter, open-label L-MIND clinical trial. The primary endpoint of this trial was objective response rate (ORR). The best ORR, achieved at any time during the study, was 56.8% (95% confidence interval: 45.3%–67.8%), and the median duration of response was 34.6 months (95% confidence interval: 26.1–not reached). The most frequently reported adverse events by system organ class were infections and infestations (72.8%; grade ≥3: 29.6%), blood and lymphatic system disorders (65.4%; grade ≥3: 56.8%), gastrointestinal disorders (64.2%; grade ≥3: 2.5%), and general disorders and administration site conditions (58.0%; grade ≥3: 8.6%). The aim of this article is to summarize the scientific review of the application which led to the positive opinion by the CHMP.